Analisis Perbandingan Kelompok Usia Korban Kekerasan Seksual Terhadap Anak Di Rumah Sakit Tk.1 Bhayangkara Raden Said Sukanto - Suryo Wijoyo; Farah Primadani Karouw; Gaby Paskalis Sirait (PT. Hasba Edukasi Mandiri, 2025)
Adults or adolescents who commit sexual violence against minors is a violation of human rights called human rights. Child protection is a legal issue in Indonesia; this is regulated in Law Number 23 of 2002 concerning Child Protection. The purpose of this study was to determine the age comparison of victims of sexual violence with children in TK.1 Bhayangkara Raden Siaid Sukanto hospital. The type of research used in this study is mixed method or mixed method. Using a concurrent triangulation strategy where researchers collect quantitative and qualitative data concurrently (at one time), then compare these two databases to find out if there is convergence, differences or some combination. The results of the study said that the most common type of sexual violence committed was lewd acts (41.8%). It was noted that the majority of perpetrators were other people known to the victim (69.5%). The majority had experienced sexual violence once (41.8%). The results of this study are relatively identical to the findings reported by KOMNAS PPA. It was found that during 2022 there were 11,686 cases of sexual violence against children in Indonesia, the majority of which were acts of sexual abuse. It was also found that the majority were other people known to the victim, followed by family members of the victim. The majority of victims of sexual violence examined at the National Police Hospital in 2022 were female (92.1%). The average age of male victims was 9.64 ± 3.67 years, while the average age of female victims was 12.28 ± 3.82 years.